Role of CYP17 rs743572 Polymorphism in Benign Prostatic Hyperplasia: A Multivariate Integrated Analysis - Weng, Hong; Fang, Cheng; Geng, Pei-Liang; Jin, Ying-Hui; Zeng, Xian-Tao; Wang, Xing-Huan (Frontiers in Physiology, 2019)
Objective: Many published studies have investigated the association between CYP17 rs743572 polymorphism and benign prostatic hyperplasia (BPH) susceptibility but have yielded inconsistent results. Hence, we performed this meta-analysis using the multivariate statistic method to address a more precise association. Methods: Case-control or cohort studies with adequate genotype distribution or minor allele frequency (MAF) were identified by searching the PubMed, Embase, and Web of Science databases up to December, 2018. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the association between CYP17 rs743572 polymorphism and BPH susceptibility. Results: Pooled MAFs of 13 studies were 37% in Caucasians and 56% in Orientals, respectively. Pooled results of 8 studies suggested that CYP17 rs743572 was not associated with the BPH susceptibility in the overall population (OR = 0.98, 95% CI: 0.80–1.20 for A2 vs. A1; OR = 0.99, 95% CI: 0.79–1.25 for A1/A2 vs. A1/A1; OR = 0.97, 95% CI: 0.62–1.53 for A2/A2 vs. A1/A1). Sensitivity analysis showed the results were robust. Subgroup analysis based on ethnicity suggested that, in Orientals, A2 allele carriers had a 28% lower risk of developing BPH compared with A1 allele carriers, and the risk of BPH is 47% lower in A2/A2 genotype carriers compared with A1/A1 genotype carriers. No significant association was observed in Caucasians. Conclusion: In conclusion, our study indicates a negative association between CYP17 and BPH in Orientals. However, due to limited sample size, the conclusion should be interpreted with caution.